Prevalence and Characterization of Internet Addiction among College Students at Sultan Qaboos University and its Association with Depression - Asma Ali Al Salmani; Nouf Al Alawi; Shahd Al Khamisi; Roaa Thani Mohammed Al Bahri (Liaquat National Journal of Primary Care)
Background: Internet addiction (IA) poses a growing concern among young people, adversely affecting their personal, academic, and professional lives. Objective: This study aimed to assess the prevalence of IA and its correlates among college students at a major public university in Muscat, Oman. Furthermore, the study aimed to investigate the potential link between IA and depression within the surveyed population. Methods: A cross-sectional study was conducted at Sultan Qaboos University (SQU) in Muscat, Oman. Data were collected using a multi-part, self-reported questionnaire. It was conducted from January 2023 until June 2024 Degree of IA severity was assessed using the 20-item Internet Addiction Test, while depression was screened using the 9-item Patient Health Questionnaire (PHQ-9). Results: A total of 1,036 SQU students participated in the study, of which 67.7% were female. The mean age was 20.4 ± 1.7 years with range of 18-25 years. The overall prevalence of IA was 53.6%, with 40.3% exhibiting mild, 12.6% moderate, and 0.6% severe IA. While IA was more common among female students, no significant association was found between IA and any sociodemographic or academic variables. However, a significant association was observed between IA and depression, with 46.7% of students with IA displaying symptoms of depression compared to 18.7% without IA with (OR=4.028, 95% CI: 3.011-5.388, p<0.001) Conclusion: This study revealed a notable prevalence of IA, with over half of all surveyed SQU college students exhibiting symptoms of internet addiction. Additionally, a significant association was found between IA and depression, underscoring the importance of addressing both IA and its associated psychological comorbidities for promoting student well-being.